Prospects and Challenges of Crowdfunding as an Alternative Funding Option in Nigeria - Abdulmajeed M.R. Aderemi; Sri Maulida; Abdullateef Abdulqadir Maikabara (IAIN Salatiga, 2021)
This study aims to review the concept, prospects, and challenges of crowdfunding in Nigeria. Furthermore, it adopts a library-based concept in which secondary sources are relied on data collection using descriptive and deductive approaches of analysis. The results showed that Nigeria has the potential of becoming the hub center of crowdfunding in Africa. However, various challenges are facing the growth of this platform as a means of ﬁnancing. These include the issues of regulation, lack of adequate awareness, as well as fraud and corruption. Furthermore, this study recommends the need for adequate awareness about crowdfunding and the regulation to ensure its functionality. It also oﬀers additional literature as a means of ﬁnancing, especially from the Nigerian context.